2021
DOI: 10.1186/s42523-021-00115-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally enriched housing conditions affect pig welfare, immune system and gut microbiota in early life

Abstract: Background Conventional pig housing and management conditions are associated with gastrointestinal pathophysiology and disease susceptibility in early life. Developing new strategies to reduce both therapeutic and prophylactic antibiotic use is urgent for the sustainable swine production globally. To this end, housing methodology providing effective environmental enrichment could be a promising alternative approach to reduce antibiotic usage, as it has been proven to positively influence pig we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…Alternatively, or in combination with external bacterial variation, there may have been an interplay between the behavior of the pullets and the colonization process for their microbial communities. Recent evidence from pigs, reported that enriched housing affected microbiota colonization relative to standard control housing (Wen et al, 2021), although this effect was not confirmed across other research (Saladrigas-García et al, 2021). The inclusion of enrichment in the pens resulted in some variation across the rearing period in exhibited behaviors (Campbell et al, 2022), responses to fear tests (Campbell et al, 2021), and body weight (Campbell et al, 2020c).…”
Section: Discussionmentioning
confidence: 94%
“…Alternatively, or in combination with external bacterial variation, there may have been an interplay between the behavior of the pullets and the colonization process for their microbial communities. Recent evidence from pigs, reported that enriched housing affected microbiota colonization relative to standard control housing (Wen et al, 2021), although this effect was not confirmed across other research (Saladrigas-García et al, 2021). The inclusion of enrichment in the pens resulted in some variation across the rearing period in exhibited behaviors (Campbell et al, 2022), responses to fear tests (Campbell et al, 2021), and body weight (Campbell et al, 2020c).…”
Section: Discussionmentioning
confidence: 94%
“…In growing pigs, the supply of manipulable materials can aid in reducing the incidence of tail biting [ 37 , 131 , 132 ]. Recent work showed that environmental enriched housing could have positive effects on the development of the immune system and the establishment of gut microbiota in early life [ 133 ]. Enabling sows to build a nest and offering straw during farrowing and lactation can prevent skin and claw lesions in piglets [ 134 ], increase activity, and reduce abnormal behaviour in the sows [ 135 ].…”
Section: Improving Housing Environment and Management Practices To Re...mentioning
confidence: 99%
“…Straw, or other organic materials, may also have a beneficial effect by manipulating the development of the gut microbiota and their influence on immune competence, potentially reducing the need for antibiotics [ 34 ]. Microbiota composition can regulate the digestion and absorption of nutrients, and resistance to pathogen colonisation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other organic enrichment products may potentially elicit a similar response, although further experiments would be required for confirmation. A recent study using straw, moist peat, wood shavings, jute bags, and branches of a broom as environmental enrichment found that this enrichment positively drives important aspects of the development of the immune system and the establishment of gut microbiota in early life [ 34 ].…”
Section: Discussionmentioning
confidence: 99%